2022
DOI: 10.1007/s11665-022-06846-w
|View full text |Cite
|
Sign up to set email alerts
|

High-Strength Near-Beta Titanium Alloy Fabricated by Direct Hot Pressing of the Machining Swarf

Abstract: Significant amount of Ti-5553 alloy (a near-beta titanium alloy) swarf is produced during the daily operation of manufacturing high strength titanium alloy components used in industry. However, the direct use of the produced swarf is seldom investigated and reported. In this paper, hot pressing was used to recycle Ti-5553 machining swarf to turn the waste into useful material. The hot-pressed Ti-5553 alloy has an ultimate tensile strength (UTS) of 675 ± 12 MPa, strain to fracture of 0.98 ± 0.04%, and bending s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Castro et al [237] used HPT to fabricate different Mg-Zn composites at room temperature. Guo et al [238] hot-pressed Ti-5553 alloy chips and…”
Section: Cyclic Extrusion Compression (Cec)mentioning
confidence: 99%
See 1 more Smart Citation
“…Castro et al [237] used HPT to fabricate different Mg-Zn composites at room temperature. Guo et al [238] hot-pressed Ti-5553 alloy chips and…”
Section: Cyclic Extrusion Compression (Cec)mentioning
confidence: 99%
“…Castro et al [237] used HPT to fabricate different Mg-Zn composites at room temperature. Guo et al [238] hot-pressed Ti-5553 alloy chips and observed the strain to fracture of 0.98 ± 0.04%, ultimate tensile strength (UTS) of 675 ± 12 MPa, and bending strength of 1181 ± 28 MPa. Later, they double-aged samples at 600 • C for 4 h followed by 700 • C for 0.5 h, and they observed the strength and ductility of the hot-pressed Ti-5553 alloy to have significantly improved, with a UTS of 1425 ± 12 MPa, strain to fracture of 2.47 ± 0.07%, yield strength (YS) of 1390 ± 20 MPa, and a bending strength 2565 ± 35 MPa.…”
Section: High Pressure Torsion (Hpt)mentioning
confidence: 99%